EFFECTIVENESS OF COMPOST AND MICROBIAL-ENRICHED COMPOST TO SUPPRESS POWDERY MILDEW AND EARLY BLIGHT DISEASES IN TOMATO - N. Istifadah; A. R. Firman; M. F. Desiana (Journal of Animal and Plant Sciences, 2020)
Compost and its water extract have the potential to suppress plant diseases. This study aimed to compare the effectiveness of compost and compost enriched with antagonistic fungi (compost plus) in controlling powdery mildew and early blight diseases in tomatoes, in the greenhouse and in the field. Compost and compost plus were applied as water extract sprayed onto the leaves every three or seven days, with or without combination with its applications in the planting media. The results showed that the microbial-enriched compost resulted in better disease suppression than the non-enriched compost. The application of compost or compost plus to the growth medium enhanced the effects of the water extract sprayed on the leaves. The compost plus incorporated in the nursery medium and planting holes, as well as spraying the water extract on the leaves every three or seven days, suppressed powdery mildew and early blight diseases by 41–49%. This study revealed that even though the enriched compost was intended for controlling soilborne diseases, their water extract can also be used for controlling airborne diseases.
Keywords: antagonistic fungi; field-grown tomato; compost plus; water extract